دراسة عيادية حول التوظيف النفسي لدى النساء المعفنات من طرف الزوج - تالية حليس; سميحة شعيب; عبد الكريم صحراوي (My University, 2021)
This study aims to know the impact of the employee’s family and professional conditions on his job performance within the institution. This study also seeks to know the most important external conditions for the worker and the need to improve the conditions of workers and improve their job performance. These goals we conducted a field study on the sample of employees of the Directorate of University Services in Laghouat, estimated at 80 employees We collected information through a questionnaire and used the descriptive approach to study this topic, and after collecting the data tab, we reached the following results: - We found through this study that family conditions (stability - family income - housing situation) have an impact on the job performance of the worker within the institution. We also found that the occupational conditions surrounding the worker also affect his performance Family conditions - professional conditions - employee - job performance